Grid connected photovoltaic systems power quality improvement using adaptive control strategy. (2017) - Logeswaran, T.; Senthilkumar, A.
In this paper, an innovative adaptive technique for power quality (PQ) improvement in grid linked photovoltaic (PV) mechanism is launched. The novel adaptive technique constitutes the integrated accomplishment of the mighty artificial bee colony (ABC) algorithm and the proportional integral derivational (PID) controller. The major objective of the proposed method is to forecast the adaptive gain parameters for the usual and anomalous scenarios in the grid side. In the proposed method, the ABC optimises the gain parameters of the PID controller for diverse grid power variations by employing the objective function, which is devised in accordance with the error minimisation between the actual grid parameters and set point grid parameters. According to the optimised gain parameters of the PID controller, the PQ of the grid side has been augmented. Thereafter, the proposed method is executed in the MATLAB/Simulink platform and the efficiency in execution is evaluated by means of analysis a contrast with the conventional approaches.